Pelatihan dan Pendampingan Pengolahan dan Packaging Kopi Bagi Petani Kecil Di Kabupaten Blitar Jawa Timur: Training And Assistance In Coffee Processing And Packaging For Small Farmers In Blitar District, East Java - Andriatmoko, Novil Dedy (Fakultas Pertanian Universitas Brawijaya, 2025)
Blitar Regency, as one of the robusta coffee producing areas, faces common problems such as the lack of knowledge of post-harvest technology, lack of packaging quality, and the selling value of farmers' products. Community service activities were conducted with the aim of increasing the capacity of smallholder farmers in Blitar Regency in terms of coffee processing and packaging. The activity was carried out with a participatory and educative approach involving 50 farmers from three main coffee-producing districts. The workshop covered fermentation techniques, drying, roasting, to modern packaging design and marketing strategies. The results showed significant improvements in participants' knowledge and skills, with post-test scores increasing 42% from the pre-test. The main constraints found were limited infrastructure, capital, and market access. As a long-term solution, sustainable mentoring, the improvement of market access through e-commerce, and the establishment of coffee processing centers at the district level are suggested. This program is proven to have a positive impact on improving product quality and farmers' welfare and has the potential to improve the regional economy.